Competing Values in the Integrated Environmental Management Process ~ Understanding the Dynamics Between Evidence Versus Value-Based Decision-Making - Davis, Nerhene (University of Pretoria, 2018)
Mini Dissertation (MA) University of Pretoria, 2018.